La doble pandemia: violencia de género y COVID-19 - Hawie Lora, Illian (2021)
Through this article the author carries out an analysis regarding the existing relation between the COVID-19 pandemic and gender-based violence, which, in both cases, woman of all ages and all socioeconomic status are the most affected. Furthermore, the author shows how other countries are dealing with the situation and presents gender perspective proposals in order to overcome the pandemic and generate a positive change regarding the unequal relations between men and women.